(untitled) (Journal of Parents and Teachers, 2018)
This article addresses the controversial issue of the use of the mathematics textbook in the classroom. Controversial because, although it is a didactic resource for teaching, it sometimes blocks the entrance of other methodologies. A series of criteria are given on what the authors consider a good textbook should be. Without rouling out that these tips could also serve publishers who, although they are eager to offer interesting and innovative products, do not always succeed.